PEMBERIAN KOMPOS AMPAS TAHU DENGAN URINE SAPI PADA PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) DI PRE-NURSERY - Hendri Betman Gultom; Sampoerno '; Gulat M.E Manurung (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Tofu waste compost and cow urine is a type of organic fertilizer which can improve the availability of nutrients for plant growth. This research was conducted at the experimental farm of the Faculty of Agriculture University of Riau began in October 2013 - January 2014 with the aim of knowing the effect of tofu waste compost with cow urine on the growth of seedlings of palm oil (Elaeis guineensis Jacq) in the Pre-Nursery. This research was conducted by the method of completely randomized design (CRD) non-factorial consisting of 12 treatments and 3 replications is follows: KU1 = 10 g of tofu waste compost with 10% of cow urine/polybag, KU2 = 10 g of tofu waste compost with 20% cow urine/polybag, KU3 = 10 g of tofu waste compost with 30% of cow urine/polybag, Ku4 = 10 g of tofu waste compost with 40% of cow urine/polybag, KU5 = 15 g of tofu waste compost with 10% of cow urine/polybag, KU6 = 15 g of tofu waste compost with 20% of cow urine/polybag, KU7 = 15 g of tofu waste compost with 30% of cow urine/polybag, KU8 = 15 g of tofu waste compost with 40% of cow urine/polybag, KU9 = 20 g tofu waste compost with 10% of cow urine/polybag, KU10 = 20 g of tofu waste compost with 20% of cow urine/polybag, KU11 = 20 g of tofu waste compost with 30% of cow urine/polybag, KU12 = 20 g of tofu waste compost with 40% cow urine/polybag. The study consisted of 36 experimental units. Each experimental unit consisted of 2 seeds, thus the total number of palm oil seedlings were 72 rods. The data were statistically analyzed and followed by test Ducan's New Multiple Range Test (DNMRT) at the level of 5%. Parameters measured were seedling height (cm), number of leaves (strands), the diameter of the stem weevil (mm), primary root length (cm), secondary root length (cm), root volume (ml) and oil palm seedling dry weight (g ). The results showed that administration of tofu waste compost with cow urine can increase the growth of  palm oil seedlings in the Pre-Nursery. Keywords: palm oil, tofu waste compost and cow urine.